A study of clinico-immunological response to art in HIV infected children in western Rajasthan - Verma, Suresh Kumar; Mourya, Harish Kumar; Mourya, Saroj; Nangal, Laxman (International Journal of Contemporary Pediatrics, 2017)
Background: Study of clinico immunological response to antiretroviral drugs in HIV infected children. Methods: 50 HIV positive children after immunological categorization put on first line pediatric ART treatment according to pediatric ART NACO guideline, side effect, clinical response (in the form of change of WHO clinical staging), and immunological response (in the form of change of CD4 count, and immunological staging) were noted on follow up study. Results: The Correlation between WHO clinical staging and immunological staging was poor so initiating anti retro viral treatment should be preferably based on CD4 count. Children who were initiated on ART have a significant improvement in both WHO clinical and immunological staging at the six and twelve months follow up and ART found to be well tolerated. Conclusions: Significant clinical and immunological improvement occur in the children who were put on ART based on CD4 counts provided if the adherence level is very good.